2019
DOI: 10.9734/jamps/2019/v21i130122
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication: Prevalence among Undergraduates in Kathmandu Valley

Abstract: Background: Self-medication is defined as the use of medicines to treat self-recognized or self-diagnosed conditions or symptoms, instead of seeking advice from professionals. Aim: Our study was aimed to assess knowledge, attitude and practice of self-medication among undergraduates in different colleges of Kathmandu valley. Methods: Descriptive cross-sectional study was carried out among undergraduates of Kathmandu valley. A semi-structured questionnaire was distributed to students in 4 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The majority of the study participants stated that they preferred self-medicine because of the minor nature of the illness followed by easy accessibility to pharmacy store, time-saving, previous experience with the same disease and less cost for selfmedication than visiting health facilities. Similar indings were reported in other studies (Baral et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the study participants stated that they preferred self-medicine because of the minor nature of the illness followed by easy accessibility to pharmacy store, time-saving, previous experience with the same disease and less cost for selfmedication than visiting health facilities. Similar indings were reported in other studies (Baral et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In developing countries, prevalence varies from 8.3% to 87% (Parulekar et al, 2016). In the case of Nepal, few studies conducted in different regions of the country reported a prevalence rate in the range of 38.2% to 94.9% (Paudel and Aryal, 2020;Parajuli et al, 2019;Baral et al, 2019). The willingness of SM practice has been attributed to the unaffordability of treatment, easy access to medicine, the time factor, unawareness, previous experience, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, ease of availability to health care services is challenging and/or expensive, thus self-medication may offer an easier and cost-effective opportunity to the consumers [ 10 ]. Furthermore, in Nepal like many other countries in the South East Asia region, prescription only medications are often dispensed by non-medical staff at medical stores without a prescription [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of having some preferable advantages of self-medication, there are some critical issues that must be explored before promoting the potential benefits of self-medication. Numerous studies have been conducted in Nepal to understand the self-medication practices of general people [ 10 , 12 , 13 , 14 ]. However, very limited data are available on health care facilities, comprising the practice of self-medication among freshman students in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the general population but studies involving students have also shown high incidence of self-medication (16). In medical students despite the fact that they are aware of its harmful effects, self-medication is common (17). Medical Students when start attending their clinical postings start thinking that they can write prescriptions and have enough knowledge to prescribe drugs to themselves and others.…”
Section: Introductionmentioning
confidence: 99%